Analisis Laporan Keuangan Pada PT Mustika Ratu Dan PT Viva Menggunakan 5 Rasio Keuangan - Dika Candra Laili; Dyah Ayu Pramesti; Khansa Tsabita Wijaya; Novia Paramida; Hanif Dwi Hastungkara (BADAN PENERBIT STIEPARI PRESS, 2024)
Financial report analysis is a process of researching financial reports and their elements which aims to evaluate and predict the financial condition of a company or business entity and also evaluate the results that the company or business entity has achieved in the past and present. It is very important for parties who have an interest in the development of a company to know the financial condition of a company, such as external and internal parties. Financial reports are an information medium used by a company to report the condition and financial position of the company to interested parties, namely internal and external parties of the company which are useful for these parties in making economic decisions. The method we use in this research is qualitative